- Penerapan Strategi Listen-Read-Discuss (LRD) untuk meningkatkan Pemahaman Membaca Siswa: - - Hafizhah Husniyah; Acep Bahrum Kamil; Totoh Tauhidin Abas (ELP (Journal of English Language Pedagogy), 2026)
This study was conducted to address the low reading comprehension skills of junior high school students, which highlight the need for more interactive and collaborative learning strategies. The purpose of this study was to describe the application of the Listen-Read-Discuss (LRD) strategy in reading instruction and to examine how this strategy can enhance students' reading comprehension skills. This study employed a qualitative approach with a classroom action research design, implemented across three learning cycles involving 32 seventh-grade students at SMPN 03 Cibarusah, Bekasi Regency. Data were collected through observation and interviews, and analyzed using thematic analysis. The results revealed that the implementation of the LRD strategy improved students' focus, participation, and ability to comprehend descriptive texts. Each stage of this strategy played a complementary role—the listening stage helped students understand the context, the reading stage reinforced their comprehension of the text content, and the discussion stage promoted meaning clarification and collaboration among students. Challenges such as distractions and limited vocabulary were minimized through active and collaborative discussion activities. Overall, the LRD strategy proved effective in fostering more interactive and participatory reading instruction and can serve as an alternative approach for teachers to enhance students' reading comprehension at the junior high school level.